A SECURE LOCKBOX TECHNIQUE FORENHANCED SHARED SHARING FOR USERS INFORMATION PACKETS ACCESS CONTROL IN CLOUD COMPUTING - ER. RAHUL PANTH; PROF. SHWETA SHRIVASTAVA; DR.VINEET RICCHARIYA (International Journal of Innovations in Engineering Research and Technology, 2021)
Cloud computing[12]and its security with user’smulti-label data is provided security by different module by different author. The security in terms which provided either encryption or in terms of hashing which aims to provide integrity verification. In this paper a lock box technique which aims to provide a highly secure mechanism for data sharing and its authenticity maintainis proposed.That technique uses proxy re-encryption and lazy encryption technique to provide an enhanced encrypted. Thattechnique leads in data processing using data hiding andkey sharing among the given selected user. The result were monitored in terms of computation time at server end and also security measures which claims the high level of security is provided in the proposed work. Our work is deems to be an innovative workwith cloud security and its architecture